2017
DOI: 10.1037/ser0000116
|View full text |Cite
|
Sign up to set email alerts
|

A national evaluation of homeless and nonhomeless veterans’ experiences with primary care.

Abstract: Persons who are homeless, particularly those with mental health and/or substance use disorders (MHSUDs), often do not receive continuous primary care services. In addition, negative experiences with primary care might contribute to homeless persons’ avoidance and early termination of MHSUD treatment. The patient-centered medical home (PCMH) model aims to address care fragmentation and improve patient experiences. How homeless persons with MHSUDs experience care within PCMHs is unknown. This study compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…Patient experience survey results and narrative data lead to the understanding of the level of patient‐centered care, which informs healthcare organizations where to place their financial and human capital for improvements. Several research teams investigated patient experience from the perspective of persons who lacked consistent housing. The separate research teams tested different service delivery models and used patients’ survey results to evaluate the model’s effectiveness in facilitating patient‐centered care .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient experience survey results and narrative data lead to the understanding of the level of patient‐centered care, which informs healthcare organizations where to place their financial and human capital for improvements. Several research teams investigated patient experience from the perspective of persons who lacked consistent housing. The separate research teams tested different service delivery models and used patients’ survey results to evaluate the model’s effectiveness in facilitating patient‐centered care .…”
Section: Resultsmentioning
confidence: 99%
“…Several research teams investigated patient experience from the perspective of persons who lacked consistent housing. The separate research teams tested different service delivery models and used patients’ survey results to evaluate the model’s effectiveness in facilitating patient‐centered care . Results from one patient experience study of persons with unstable housing and behavioral health diagnoses affirmed an organization’s practice to employ clinicians who valued humanistic care .…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent study, homeless veterans reported more negative primary care experiences than housed veterans across seven of eight domains of care. These negative experiences applied not only in interpersonal domains but also in veteran perception of the thoroughness of treatment and their role in medication decision-making [ 76 ]. In some cases, homeless veterans reported delaying entry into primary care services due to a lack of trust in providers and perceived stigma as a result of their homelessness status [ 77 ].…”
Section: Barriers To Access and Interventions/tools By Dimensionmentioning
confidence: 99%
“…Individuals experiencing homelessness face unique challenges in obtaining appropriate primary care: perceived stigma, lack of trust, negative experiences with care coordination, as well as logistic barriers such as ability to pay, lack of transportation, and pressure from competing priorities (Gelberg et al, 1997; Gruenewald et al, 2018; Jones et al, 2017; Ramsay et al, 2019; Wen et al, 2007). Over the last four decades, federal and nonfederal programs have sought to deliver primary care that is more responsive to their needs (Gabrielian et al, 2017; Jones et al, 2018; O’Toole et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these numerous efforts at addressing access to primary care, reports suggest that persons experiencing homelessness continue to have serious problems accessing primary care and that they have inferior experiences even when care is obtained (Baggett et al, 2010; Jones et al, 2017; Kertesz, McNeil, et al, 2014). Efforts to improve the design and delivery of primary care for persons who are homeless could be enhanced by a better understanding of what indicates quality in primary care, from the viewpoints of patients who are homeless and experts who have focused their careers on this population.…”
Section: Introductionmentioning
confidence: 99%